Menggali Pola Komunikasi Antarbudaya Bajo-Bugis dan Sikka-Krowe di Wuring-Maumere: Studi atas Hibridasi Budaya - Anjelinus Sandri; Felix Riondi Sugar; Evaristus Jemparus; Dionisius Rienaldi Pea Muga; Leonardus Roland Mite Ajo; Fransiskus Mario Milenitri Hengky; Silverius Triwira Juniarto Evan Muda; Bonifasius Steven Mau (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
The Bajo-Bugis tribe in Wuring, Maumere, has long lived and settled on the north coast of Flores island. He entered the Tana Sikka nian not in a vacuum, there has been a deeply rooted Sikka-Krowe culture. The meeting of the two cultures gave birth to a new Bajo-Bugis tribal culture. On the other hand, the pattern of communication, the way of life and culture of the Bajo-Bugis tribe has been patterned Sikka is not entirely different and is uprooted from the culture of the original Bajo tribe in Sulawesi. Through the analysis of the scope of communication patterns, the author found how the combination of the Bajo-Bugis tribe and the Sikka-Krowe tribe on the north coast of Flores Island was without dominating each other. This study uses a literature review method and observation. From this research it can be found that the scope of intercultural communication patterns, Bajo-Bugis and Sikka-Krowe, can blend with each other and live together without dominating each other. Value selectivity in the conclusion section is a method of fusion or hybridization between two cultures so as to create new communication patterns. This article also contains some suggestions that must be considered.